THE EFFECT OF ADMINISTERING PROBIOTIC IN DRINKING WATER ON PERFORMANCE OF BALI DUCKS FED RATION CONTAINING GREEN BEANS SPROUTS PEELS FLOUR - N. K. D. D., Santi; Siti, N. W.; Sukmawati, N. M. S. (Jurnal Peternakan Tropika, 2020)
The study aims to determine the effect of administering probiotics in drinking water on performanceof bali ducks fed rations containing green bean sprouts peels flour was conducted at the Faculty of Animal Husbandry Farm, Udayana University, located on Jalan Raya Sesetan Gang Markisa no 5, Sesetan, Denpasar, Bali for 8 weeks. The experimental design used was a completely randomized design (CRD) with 3 treatments and 5 replications, so there were 15 experimental units. Each experimental unit used 3 female bali ducks with a body weight range of 46.98 ± 7.18 g. The treatments were : ducks given drinking water without probiotics as a control (A), ducks given drinking water + 2,5 ml of probiotics (B), ducks given drinking water + 5 ml of probiotics (C). The variables observed were : ration consumption, drinking water consumption, initial body weight, final body weight, weight gain, and Feed Convertion Ratio (FCR). The results of this study showed that in general the performance of ducks that were given probiotics tended to be higher than the controls as the increasing of the levels given, but statistically not significantlydifferent (P>0,05). Based on the results of this study it can be concluded that the administration of combination probiotic Bacillus subtilis strain BR 2 CL and Bacillus sp . strain BT 3 CL in drinking waterat the level of2,5 ml and 5 ml/head/day not yet improve the performance of female bali ducks 8 weeks of age fed ration containing green been sprout peel flour.   Keyword: bali ducks, performance, probiotic, green beans sprouts peels